2018
DOI: 10.1080/10408398.2018.1500441
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fourier transform infrared spectroscopy for the quality and safety analysis of fats and oils: A review

Abstract: Fats and oils are essential food components. Their quality and safety pose major concerns for consumers and food producers because of factors such as oxidation and rancidity, excessive levels of trans fatty acid (TFA), and widespread adulteration. Thus, a rapid and easy-to-use technique must be exploited for quality parameter evaluation and monitoring to ensure the edibility, safety, and quality of fats and oils. In the last decades, Fourier transform infrared (FTIR) spectroscopy has shown great potential in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 98 publications
0
23
0
Order By: Relevance
“…Over the past few decades, Fourier transform infrared (FTIR) spectroscopy had provided a reliable analytical tool in the fat and oil industries and become an attractive alternative to traditional methods, being a rapid and easy-to-use technique to evaluate qualitatively or even quantitatively the oils' edibility, their intrinsic quality parameters, safety, as well as authenticity, traceability and adulteration [1][2][3][4][5][6][7]. Moreover, the determination of edible oil authenticity, compared with the more accurate but time-consuming, laborious, and expensive chromatography-based method is advantageous as a more rapid and cheaper solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few decades, Fourier transform infrared (FTIR) spectroscopy had provided a reliable analytical tool in the fat and oil industries and become an attractive alternative to traditional methods, being a rapid and easy-to-use technique to evaluate qualitatively or even quantitatively the oils' edibility, their intrinsic quality parameters, safety, as well as authenticity, traceability and adulteration [1][2][3][4][5][6][7]. Moreover, the determination of edible oil authenticity, compared with the more accurate but time-consuming, laborious, and expensive chromatography-based method is advantageous as a more rapid and cheaper solution.…”
Section: Introductionmentioning
confidence: 99%
“…Different reviews [5,27] and experimental data have been reported, about the FTIR spectroscopy applied for the characterization of edible (especially olive) oil quality [10,26,28,29], as well as for the freshness evaluation [24] and detection of adulteration [4,12,[30][31][32]. A large majority of data refer to olive oil adulteration with low cost edible oils [28,33,34] or to assess oil oxidation [6,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The peak at 721 cm −1 corresponds to the CH 2 rocking mode . Given that the signal obtained by the PE‐film‐based FTIR method is ≈20–40 times greater than that obtained by the ATR–FTIR method, the detection precision of the PE‐film‐based FTIR method is higher than that of the ATR–FTIR method …”
Section: Resultsmentioning
confidence: 97%
“…Oxidation of lipids is a major cause of deterioration of the quality of foods affecting flavor, color, texture, and even the nutritional value and safety. Safety is of particular concern when speaking of ultra-processed and frying foods, in which further degradation reactions may occur with the formation of toxic compounds [23,24].…”
Section: Colors and Flavors Of Main Tocolsmentioning
confidence: 99%